Stanovništvo Osijeka i njegovo ekonomsko stanje 1828. godine - Sršan, Stjepan (Array, 1990)
In his exhaustive study the author analyzes numerous and varied (quantitative) data on the population of Osijek in the first half of the 19th century. Special attention is paid to the population structure which was very heterogeneous and complex. Family names, social status and material conditions of the Osijek families are listed. The paper is based on the archival sources published for the first time